2012
DOI: 10.1016/j.forsciint.2012.08.018
|View full text |Cite
|
Sign up to set email alerts
|

Differentiation of lipsticks by Raman spectroscopy

Abstract: Dispersive Raman spectra have been obtained using a Raman microscope and an excitation wavelength of 632.8 nm from 69 lipsticks of various colours and from a range of manufacturers without any pre-treatment of the samples. 10% of the samples were too fluorescent to give Raman spectra. 22% of the samples gave spectra which were unique to the brand and colour within the collected sample set. The remaining 68% of the samples gave spectra which could be classified into seven distinct groups.Discrimination of red l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(19 citation statements)
references
References 9 publications
0
19
0
Order By: Relevance
“…Previous work has reported assignments of peaks to some of the compounds commonly found in lipsticks. 10 Further identification of components and assignment of peaks have also been published. 11 Fluorescence due to the underlying glass was observed between 1200 and 2000 cm -1 when the smears were analysed using the 784 nm laser.…”
Section: Effects Of Changing the Excitation Wavelength On Fluorescentmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous work has reported assignments of peaks to some of the compounds commonly found in lipsticks. 10 Further identification of components and assignment of peaks have also been published. 11 Fluorescence due to the underlying glass was observed between 1200 and 2000 cm -1 when the smears were analysed using the 784 nm laser.…”
Section: Effects Of Changing the Excitation Wavelength On Fluorescentmentioning
confidence: 99%
“…9 We have previously demonstrated that Raman spectroscopy is a valuable technique for the identification and differentiation of a large range of lipstick samples under controlled laboratory conditions. 10 However forensic evidence is rarely found in ideal conditions. It is often found in trace amounts on different substrates which have been exposed to variable environmental conditions.…”
Section: Introductionmentioning
confidence: 99%
“…The effectiveness of such research depends, therefore, on the type of technique used and its discriminatory possibilities concerning the tested material. There are a lot of modern analytical methods (nondestructive [3][4][5][6][7][8][9][10][11] and destructive [3,[12][13][14][15][16][17][18][19][20][21][22][23]) that have been used in the forensic examination of lipsticks. These methods have been summarized and critically compared regarding the advantages and disadvantages in one review article [24].…”
Section: Introductionmentioning
confidence: 99%
“…The largest number of articles on the discriminant analyses of lipsticks describes the use of Raman spectroscopy (RS) [5][6][7][8][9]. In these publications [5][6][7][8][9], RS is presented as a simple and quick technique that does not require any sample preparation. Spectra can be recorded in situ on the various surfaces on which the tested lipstick traces were applied.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation